Hepatitis C virus‐free endoscope procedures project: An in‐hospital elimination approach - Benjamin Lih‐Ren Hsieh; Yen‐Ting Kuo; Yu‐Ju Wei; Pei‐Chien Tsai; Ming‐Lun Yeh; Chung‐Feng Huang; Chia‐Yen Dai; Ming‐Yen Hsieh; Jee‐Fu Huang; Ming‐Lung Yu; Wan‐Long Chuang (Kaohsiung Journal of Medical Sciences)
Abstract Hepatitis C virus (HCV) elimination in the care cascades for patients receiving invasive procedures remains elusive. This study aimed to evaluate the efficacy of HCV‐free Endoscope Procedures Project (CEPP) in the effort toward hospital HCV micro‐elimination in Taiwan. An electronic medical record (EMR)‐based remind system was introduced into gastrointestinal, surgical, urological, and gynecological departments prior to the endoscopy procedures. Anti‐HCV tests were actively ordered on their EMR among those patients who have not been tested in the past 5 years. Those patients with anti‐HCV+ were recruited into the care cascade for HCV treatment, including HCVRNA testing, direct antivirals (DAAs) delivery, and treatment response assessment. We divided the elimination project into two phases: before (2020 Jan to 2020 Dec, phase A) and during (2021 Jan to 2022 Sep, phase B) the remind system. The screening rate of phase B was 64.2% (1857/2893), which was significantly higher than phase A (18.7%, 899/4812) (p < 0.001). The screening rate of Department of Medicine (DOM) significantly increased from 21.1% of phase A to 89.3% of Phase B (p < 0.001). During phase B, the screening rate of non‐DOM was 48.2%, which was significantly higher than 11.8% of Phase A (p < 0.001). During Phase B, 15 (0.8%) out of 1857 screened patients were HCVRNA+. Six HCVRNA+ patients received DAAs treatment, and all achieved viral eradication. The CEPP significantly increased the anti‐HCV screening rate for subsequent care cascades, particularly in patients of DOM.